MORPHOLOGICAL PLASTICITY AND TAXONOMIC IMPLICATIONS OF FAVITES CORALS FROM SPERMONDE ARCHIPELAGO - Andi Haerul; Neviaty Putri Zamani; Dedy Duryadi Solihin; Suharsono; Syafyudin Yusuf (Jurnal Ilmu Kelautan SPERMONDE, 2025)
Morphologycal characterstic both descriptive and morphometric, like corralite diameter, corralite shape, the presence or absence of paliform lobe, colonies surface form, and septa teeth were the key for determining the Favites coral species characters, but these character are often influenced by environmental factors. In this studi will be try to reconstructed phylogeny tree of Favites coral‟s (Favites abdita, F. benattae, F. chinensis, F. flexuosa, F. halicora, and F. paraflexuosa). The speciment collected from Spermonde Archipelago. Phylogeny tree was reconstructed based on the morphological characters (descriptive and morphometric) using UPGMA (Unweighted Pair Group Method with Arithmetic Mean) Methood on PAUP 4.0 software. The result showed the grouping of taxa for each species. However, if only using morphometric character in preparing the taxa group, it will not show the clear differences among species. This caused by the morphometric characters have the highest plasticity and influenced by environmental factors, if compared with the descriptive character.